TELEWORK AS AN EMPLOYABILITY TOOL IN COMMERCIAL COMPANIES IN CIUDAD DEL ESTE, DURING THE COVID-19 PANDEMIC - Gastón Duarte Ortigoza, Sócrates; Ulises Galeano Morínigo, Marcos; Mabel Casco Ayala, Rossana (Revista Gênero e Interdisciplinaridade, 2023)
The present research work discloses the modality of Teleworking, where and how they originated, its characteristics, the current legislation in Paraguay, not before describing the conditions that must be taken into account for its optimal implementation, as well also its evolution over the years. In addition, through Law 6738/20, State intervention is presented for its application, through MTESS, to avoid distortion in the pursuit of the investigated model. The research raises the effect on employability and consequently the effect that this puts pressure on the income of the collaborators, and therefore minimizes the effect that the lack of employment could cause in our area, a negative effect, as a result of the coronavirus pandemic. Covid-19. The field work has been raised by means of a quantitative cut, using the survey technique, with a closed question and dichotomous and multiple-choice response options. The result is presented by means of statistical graphs, according to which all the approaches made to the sample were answered. In conclusion, it was possible to verify that the hypothesis raised at the beginning of the investigation is fully fulfilled, this is evidenced by the aforementioned result.